KR desulfurization slag curing method and modified desulfurization slag prepared through KR desulfurization slag curing method
By adding Na salt and TiO2 to the KR desulfurization slag as curing agent, and subjecting to stirring and cooling, the powdering problem caused by phase transformation expansion of dicalcium silicate is solved, and the stable curing and recycling of KR desulfurization slag is achieved.
Patent Information
- Application Number
- CN202411891124.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-11
AI Technical Summary
The phase transition expansion of dicalcium silicate in KR desulfurization slag leads to pulverization, seriously polluting the environment and limiting its recycling.
Before slag, the curing agent containing Na salt was added to the KR desulfurization slag, and it was fully contacted and mixed by stirring, and then cooled below the temperature of the transition of dicalcium silicate to the gamma phase to achieve curing.
It effectively inhibits the γ-phase formation of dicalcium silicate, reduces the pulverization phenomenon, improves the storage and feeding conditions of KR desulfurization slag, and promotes its resource recycling.
Smart Images

Figure CN119592756A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-temperature steel slag treatment, and more specifically, to a solidification method of KR desulfurized slag and modified desulfurized slag prepared therefrom. Background Art
[0002] The KR method of hot metal desulfurization was invented by Nippon Steel Corporation of Japan and began to be used in industrial production in 1965. The Second Steelmaking Plant of Wuhan Iron and Steel Corporation introduced the first stirring desulfurization device in China from Nippon Steel Corporation of Japan in 1976. As time goes by, the KR method of desulfurization has been widely used and improved in China. It currently uses cheap lime and fluorite as desulfurizers for deep desulfurization and ultra-deep desulfurization, and has gradually become an important technical means used by advanced steel mills at home and abroad to produce high-quality steel.
[0003] KR hot metal pretreatment desulfurization is an important means of smelting low-sulfur special steel, which can reduce the S content of hot metal to 20PPM. The desulfurized slag obtained from KR hot metal pretreatment is called KR desulfurized slag, in which CaO and SiO2 mainly exist in the form of dicalcium silicate C2S and tricalcium silicate C3S. During the cooling process of the molten KR desulfurized slag obtained after slagging, C2S undergoes a polymorphic transformation, and successively undergoes the transformation from α-C2S, α'-C2S, β-C2S to γ-C2S. At room temperature, C2S exists in the form of γ-C2S, and the densities of α'-C2S, β-C2S and γ-C2S are 3.14g / cm 3 、3.20g / cm 3 , 2.94g / cm 3 Due to the large difference in density, a large volume effect is caused, and volume expansion occurs, with an expansion rate of 10% to 15%, which leads to pulverization of steel slag, easily forming white dust, and seriously polluting the environment. In addition, in the desulfurization reaction, the CaO in the lime powder generally cannot react fully, and its utilization rate is very low, even less than 20%. Therefore, the desulfurization slag contains more free CaO, which is active in nature and easily reacts with water vapor in the air to generate Ca(OH)2, and finally reacts slowly with CO2 in the atmosphere to generate CaCO3, which makes the CaO particles expand and burst, and also causes the white slag to pulverize.
[0004] In 2020, China's total crude steel output has exceeded 1 billion tons, and the annual output of KR desulfurization slag has exceeded 4.4 million tons. The annual increase in the stockpile of KR desulfurization slag has had an adverse impact on the normal production of metallurgical enterprises. Steel mills are currently experimenting with using the KR desulfurization slag obtained from desulfurization as a raw material for the configuration of new desulfurizers, thereby recycling resources. This not only reduces the use of desulfurizers, but also alleviates the subsequent treatment of a large amount of desulfurization slag. However, the pulverization phenomenon caused by the above-mentioned factors will not only pollute the environment, but also make the storage and feeding of desulfurization slag very difficult, thereby limiting the recycling of KR desulfurization slag. How to inhibit the pulverization of smelting steel slag has become one of the research topics in the field of high-temperature steel slag treatment. For example, the Chinese patent application with publication number CN117965825A discloses a method for solidifying KR desulfurization slag and the resulting product. The KR desulfurization slag needs to go through batching, mixing, slag pouring, and water spraying cooling steps, and finally cooled to obtain granular or block cold slag, wherein 2% to 4% cryolite and 2% to 3% boron ore are added during the batching process, and the corresponding temperature drop rate is controlled according to the slag temperature during the water spraying cooling process. This application utilizes the solid solution effect of B2O3 on dicalcium silicate, supplemented by a suitable cooling rate to solidify the KR desulfurization slag, and further utilizes the encapsulation mechanism of cryolite on free calcium oxide, the pulverization phenomenon is effectively improved, and the treated slag is granular or blocky, and the composition is basically the same as the original hot slag. However, this application requires strict control of the temperature drop rate.
[0005] For another example, the Chinese patent application with publication number CN113957202A discloses an AOD argon oxygen refined stainless steel smelting slag coagulant and its preparation method and application. The required raw materials are pearl sand 60-80wt%, industrial waste cryolite 20-40wt%, and an additional binder sodium silicate dry powder 0-1.5wt%. The required raw materials need to be crushed to less than 5mm, and then mixed and stirred in proportion. After being pressed by a granulating device, they are broken into 0.5-3mm coagulants. The coagulants are sprayed into the slag tank with the slag flow when the AOD slag is removed. In this application, the slag coagulant requires more raw materials and needs to be rolled, crushed, granulated, sieved, etc., and the composition of the AOD argon oxygen refined stainless steel smelting slag is different from that of the KR desulfurization slag, so it is not suitable for curing the KR desulfurization slag. In addition, in the past two years, there has also been a technology for curing desulfurization slag with an acidic modification agent, but the cost of using an acidic modification agent is too high, and there is a problem of incomplete curing. Summary of the invention
[0006] In view of the problem in the prior art that the phase change expansion of dicalcium silicate easily leads to the pulverization of KR desulfurization slag, the present invention provides a solidification method for KR desulfurization slag. This solution effectively solves the pulverization of KR desulfurization slag caused by the phase change expansion of dicalcium silicate by adding a solidifying agent containing Na salt to the KR desulfurization slag before slagging.
[0007] The first aspect of the present invention provides a method for solidifying KR desulfurization slag, comprising: before slagging, adding a solidifying agent into a molten iron ladle to allow the KR desulfurization slag to be fully contacted / mixed with the solidifying agent; wherein the solidifying agent comprises Na salt and TiO2; and cooling the KR desulfurization slag mixed with the solidifying agent to below the phase transition temperature of β-phase dicalcium silicate to γ-phase dicalcium silicate, thereby achieving solidification treatment of the KR desulfurization slag.
[0008] Under normal circumstances, the dicalcium silicate in KR desulfurization slag is an island silicate structure, and its structure is composed of structural units [SiO4] tetrahedron through [CaO X ] polyhedrons are connected, and the two together form a three-dimensional spatial structure. Dicalcium silicate has multiple states, and its state changes with the change of temperature and crystal system. Specifically, when the temperature is raised to 1425°C, the crystal form of dicalcium silicate exists as α-C2S; when cooled to 1421°C, α-C2S is transformed into α′-C2S; when heated to 675°C, β-C2S is transformed into α′-C2S, and when cooled to 670°C, α′-C2S is transformed into β-dicalcium silicate. Therefore, the morphological transformation of α-dicalcium silicate to α′-dicalcium silicate and the morphological transformation of α′-dicalcium silicate to β-dicalcium silicate have a lag phenomenon. As the cooling continues, at a temperature below 500°C, β-dicalcium silicate is transformed into γ-dicalcium silicate. Correspondingly, when α-dicalcium silicate transforms to α′-dicalcium silicate, half of the [SiO4] tetrahedrons rotate; during the transformation of α′-dicalcium silicate to β-dicalcium silicate, the [SiO4] tetrahedrons rotate. 2+ The coordination number also changes; when β-dicalcium silicate transforms to γ-dicalcium silicate, the rotation of [SiO4] tetrahedron and the migration of Ca atoms often occur. Since the [SiO4] tetrahedron in the structure of γ-dicalcium silicate is extremely irregular, the relative position of [SiO4] tetrahedron and Ca atom of one type site is the same, but the Ca atom of another type site is replaced. Therefore, the phase transition between α′-dicalcium silicate and β-dicalcium silicate, and between β-dicalcium silicate and γ-dicalcium silicate is considered to be semi-reconstructive. Since the rearrangement of these bonds is very complicated, the transformation will occur relatively slowly.
[0009] The hydration activity of high-temperature dicalcium silicate is relatively good. The hydration activity is ranked from high to low as follows: α-dicalcium silicate, α′-dicalcium silicate, β-dicalcium silicate, and γ-dicalcium silicate. Pure dicalcium silicate exists in the form of γ-dicalcium silicate at room temperature. 2+ The coordination number of β-dicalcium silicate is 6, while the high-temperature crystalline calcium silicate has a different coordination number and coordination environment. 2+The coordination is irregular, so there will be vacancies in its structure, resulting in defects, and then its lattice will be distorted. 2+ The coordination is regular, so β-dicalcium silicate has very good hydration activity, and the coordination number of calcium ions changes during the transformation of β-dicalcium silicate to γ-dicalcium silicate. In addition, the Ca-O ion bond in the structure of β-dicalcium silicate is weaker than that of γ-dicalcium silicate, which also leads to its higher hydration activity than γ-dicalcium silicate.
[0010] It should be noted that the addition of Na salt and TiO2 in the present invention is crucial to the modification of KR desulfurization slag. + The activity of dicalcium silicate can be effectively improved by changing its structure. The specific principle is: the grain boundary is the gathering place of defects, and the vacancy concentration is often higher than that inside the lattice. The greater the vacancy concentration at the grain boundary, the greater the lattice distortion. On the one hand, the addition of Na + It is enriched on the grain boundaries or dislocations of dicalcium silicate, reducing the defect free energy, reducing the nucleation driving force of γ-dicalcium silicate, hindering its nucleus formation, and thus improving the activity of dicalcium silicate. + Also, by supplementing Ca 2+ The reduced coordination improves the symmetry of the dicalcium silicate crystal structure, and this structure is also conducive to the formation of active dicalcium silicate. The addition of TiO2 in the present invention is crucial to further synergistically modifying the pulverization phenomenon of KR desulfurization slag. Regarding the addition of TiO2, Ti can replace Si in dicalcium silicate, the Ti-O bond is more stable, the symmetry of the [SiO4] tetrahedron is improved, the high temperature and high activity are stabilized, and the Ca 2+ The effect on the symmetry of the [SiO4] tetrahedral structure can prevent the formation of γ crystals. Therefore, the addition of Na salt and TiO2 can have a synergistic inhibitory effect on the formation of γ dicalcium silicate.
[0011] In summary, the added Na salt can inhibit the formation of γ-dicalcium silicate; at the same time, the composition of the modified KR desulfurization slag is roughly the same as that before modification, which facilitates its resource utilization.
[0012] It should be noted that the KR desulfurization slag mixed with the curing agent is naturally cooled to a temperature of 500°C, which is the temperature at which β-dicalcium silicate transforms into γ-dicalcium silicate; when the temperature drops below this temperature, the crystal proportions of β-dicalcium silicate and γ-dicalcium silicate in the dicalcium silicate are stable, and the transformation of β-dicalcium silicate into γ-dicalcium silicate no longer occurs.
[0013] Furthermore, the raw material of the Na salt is pure NaCl or industrial salt; and / or Na +The amount of Na salt added is 0.23% to 0.31% of the mass of KR desulfurized slag. In particular, industrial salt is selected to reduce the cost of the curing agent.
[0014] Furthermore, the added amount of TiO2 is 0.8-1% of the mass of the KR desulfurization slag.
[0015] Furthermore, the raw material of TiO2 is ilmenite.
[0016] Furthermore, after adding the curing agent into the ladle, the KR desulfurization slag and the curing agent are fully contacted / mixed by stirring.
[0017] Furthermore, the KR desulfurization slag and the curing agent are fully contacted / mixed by stirring, specifically, the curing agent is added to the surface of the KR desulfurization slag, and the molten iron under the KR desulfurization slag is stirred to make the KR desulfurization slag and the curing agent evenly mixed; the stirring heights are h1=0.95h, h2=0.9h, h3=0.85h, where h represents the height of the molten iron in the ladle; the corresponding stirring speeds are The unit of stirring speed is r / min. Furthermore, the stirring paddle used for stirring is a solid cross shape.
[0018] The present invention performs stirring at three heights in sequence after adding the curing agent, so that the curing agent and the KR desulfurization slag are evenly mixed. A solid cross-shaped stirring paddle is inserted into the molten iron. As the stirring paddle rotates, the molten iron is pressed toward the inner wall of the ladle along the outer surface of the stirring paddle. Then the molten iron is impacted and divided into two parts, an upward part and a downward part. The upward part of the molten iron will fall back to the position of the stirring paddle due to gravity, and then be driven and impacted again to form an annular flow; and the downward part of the molten iron will also return to the position of the stirring paddle due to the pressure difference, and then be driven and impacted, also forming an annular flow. In the process of mixing, the splashing of the curing agent must be considered. Therefore, the stirring depth during the stirring process is from shallow to deep, and the stirring speed is from slow to fast. During the initial stirring, the curing agent is initially and evenly separated, and then the stirring speed is increased as the stirring depth increases to form a large circulation to enhance the uniform effect.
[0019] Furthermore, the method further comprises: before cooling, pouring the KR desulfurization slag mixed with a curing agent into a slag pot; and / or baking the KR desulfurization slag mixed with a curing agent.
[0020] The modified KR desulfurization slag is baked. The principle is: the change of the hydration activity of CaO is a gradual process. In fact, it is essentially the transition of atoms inside the crystal. The difference in the free melting of the materials on both sides of the grain boundary is the driving force for the interface to move toward the center of curvature. Baking increases the average vibration energy of atoms, making it easier for atoms to obtain the energy required for transition, accelerating the transition of atoms, resulting in faster grain boundary movement, and more regular atomic arrangement in the crystal lattice, fewer defects, and reduced lattice distortion, so the crystal structure becomes more stable. Correspondingly, when CaO is baked, high-temperature baking makes the calcium oxide crystals more complete and dense, and even sintering occurs. As the baking process proceeds, the CaO grains will grow, their pores will become less, and the surface area will become smaller, so that the combination of calcium oxide and water will slow down, and the nucleus formation of calcium hydroxide will also be affected, making it difficult to obtain highly dispersed calcium hydroxide. By reducing the hydration activity of CaO, the problem of white slag powderization can be reduced.
[0021] Furthermore, the KR desulfurization slag mixed with the curing agent is baked, specifically, the baking temperature is selected to be 1000-1200° C., and the baking time is 45-75 minutes.
[0022] The second aspect of the present invention provides a modified KR desulfurization slag, which is prepared by the above-mentioned KR desulfurization slag solidification method. The mass fraction of dicalcium silicate phase in the modified desulfurization slag is less than 2%, and the mass fraction of γ-type dicalcium silicate phase is less than 0.8%.
[0023] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0024] (1) In the present invention, a curing agent is added to the ladle before slagging, so that the molten KR desulfurization slag and the curing agent are fully contacted or / mixed, so that the KR desulfurization slag and the curing agent are evenly mixed, and the curing agent includes Na salt, and the Na salt provides Na + It is enriched on the grain boundaries or dislocations of dicalcium silicate, reducing the defect free energy, reducing the nucleation driving force of γ-dicalcium silicate, and at the same time improving the symmetry of the dicalcium silicate crystal structure, inhibiting the transformation of high-temperature crystal form to low-temperature crystal form. Furthermore, the curing agent also includes TiO2. The Ti provided by TiO2 can replace Si in dicalcium silicate, which can prevent the formation of γ crystal form, stabilize high temperature and high activity, and at the same time improve the symmetry of the [SiO4] tetrahedron, inhibiting the transformation of β-C2S to γ-C2S crystal form. In addition, Ca 2+ Easy to break free 2- The constraints are enriched in defect sites such as grain boundaries, reducing the free energy, thereby further inhibiting the transformation of β-C2S to γ-C2S crystal form.
[0025] (2) The present invention further promotes the development of calcium oxide crystals to be more complete and dense by baking, promotes the growth of CaO grains, reduces its pores, and reduces its surface area, thereby slowing down the combination of calcium oxide and water, affecting the nucleus formation of calcium hydroxide, and making it difficult to obtain highly dispersed calcium hydroxide, thereby solving the problem of white slag powderization caused by active CaO. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the microscopic morphology of the desulfurized slag sample after solidification in Example 1 of the present invention.
[0027] Figure 2 This is the coordination diagram of γ-dicalcium silicate.
[0028] Figure 3 It is a structural schematic diagram of the stirring mechanism of the present invention.
[0029] Figure 4 This is a physical picture of KR refined slag before solidification.
[0030] Figure 5 This is a physical picture of the KR desulfurization slag after solidification in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with embodiments.
[0032] The following examples are descriptions of the curing effect of the KR desulfurization slag curing method, and should not be understood as limiting the composition of the KR desulfurization slag of the present invention. The KR desulfurization slag applicable to the curing method of the KR desulfurization slag provided by the present invention includes the following components by mass fraction: CaO: 30-60%, SiO2: 10-25%, Al2O3: 1-3%, MgO: 0.5-2%, TFe: 5-30%, S: 0.5-3.5%. In the following examples, industrial salt is selected for Na salt for economic considerations, and other Na salts such as NaCO3, NaSO4, and Na3PO4 are all acceptable, and the raw material containing TiO2 can be selected from ilmenite and pure TiO2.
[0033] The solidification rate in the present invention refers to the ratio of "the mass of the modified KR desulfurization slag obtained by cooling to room temperature after solidification" to "the sum of the mass of the KR desulfurization slag obtained by pouring slag from the ladle plus the mass of the raw material containing the solidifying agent".
[0034] Example 1
[0035] The present embodiment provides a method for solidifying KR desulfurized slag, which is carried out at operating table No. 2 of a molten iron pretreatment workshop of a steelmaking plant of Changzhou Zhongtian Iron and Steel Group Co., Ltd. in Jiangsu Province. The KR desulfurized slag of furnace No. 1 is taken, the temperature of which is 1310°C, the slag amount is 1593 kg, and the composition of the desulfurized slag is shown in Table 1. The curing agent used is Na salt and a raw material containing TiO2, wherein the Na salt used is industrial salt, and the raw material containing TiO2 is ilmenite. The above raw materials are all provided by Changzhou Zhongtian Iron and Steel Group Co., Ltd. in Jiangsu Province. The effective component of the industrial salt used is NaCl, and the effective component of the ilmenite is TiO2, wherein the effective component percentage of the industrial salt is 95%, and the effective component percentage of the ilmenite is 53%.
[0036] Table 1 KR desulfurization slag composition of Example 1 (wt%)
[0037] Component TFe CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO S other Proportion 11.51 58.12 14.45 2.38 0.7 3.2 9.64
[0038] A solidification method of KR desulfurization slag in this embodiment includes the following steps:
[0039] S1, adding the curing agent composed of the above industrial salt and ilmenite to the surface of KR desulfurization slag;
[0040] The specific amount of curing agent is calculated according to the desulfurization slag composition of the KR workshop, and the amount of industrial salt and ilmenite required is prepared. The specific calculation process of the amount of the two is as follows:
[0041]
[0042] In the above formula, M1 represents the mass of industrial salt added, ω Na is the content of Na ions in industrial salt, M 渣 is the mass of desulfurized slag, k1 is the addition coefficient of Na ions, the value range is between 0.23% and 0.31%, and 0.26% is selected in this embodiment; in the above formula, M2 represents the mass of added ilmenite, ω TiO2 is the content of TiO2 in ilmenite. k2 is the addition coefficient of ilmenite, which ranges from 0.8 to 1%, and is selected as 0.92% in this embodiment. Substituting into the above formula, the mass of industrial salt added is 11.09 kg, and the mass of ilmenite added is 27.65 kg;
[0043] S2. Stir and mix. According to the incoming mass of molten iron and the size of the ladle, calculate the stirring height, the corresponding stirring speed and the stirring time. The specific calculation process is:
[0044] The mass of the molten iron entering the station in this implementation is 316.36t, and its density is 7138kg / m 3 , the volume is 44.31m 3; Based on the fact that the ladle is in the shape of a truncated cone, R is the radius of the ladle mouth, r is the radius of the ladle bottom, and H is the height of the ladle, the height h of the molten iron in the ladle is calculated.
[0045] The structural diagram of the stirring mechanism used in this embodiment is shown in FIG. Figure 3 As shown, a cross-shaped stirring paddle is used, and the distance between the lower end surface of the cross-shaped stirring paddle and the bottom of the inner wall of the ladle is the stirring height. The stirring heights are h1=0.95h, h2=0.9h, h2=0.85h, and the corresponding stirring speed formula is The unit of stirring speed is r / min.
[0046] In this embodiment, h1 is 3.61m, h2 is 3.42m, h3 is 3.23m, the corresponding stirring speeds v1 are 74r / min, v2 are 84r / min, v3 are 94r / min, and the corresponding stirring times are 30s respectively.
[0047] S3, slag pouring: pour the reformed KR desulfurization slag into the slag pot, and plan the slag pot according to the slag volume.
[0048] S4. Send the slag pot to the slag treatment plant for baking. The baking temperature is 1100 degrees and the baking time is 60 minutes.
[0049] S5. Let the slag pot stand and cool to room temperature, then turn the slag pot over, pour the KR desulfurization slag after standing into the slag pit, keep the slag pit dry without water accumulation, and obtain modified KR desulfurization slag.
[0050] After cooling, the KR desulfurization slag is granular or blocky. The microscopic morphology is referenced to Figure 1 As shown, the actual appearance diagram is shown in Figure 5 shown.
[0051] The composition of the modified desulfurization slag was measured. After modification, the composition of the obtained desulfurization slag was roughly the same as that of the unmodified KR desulfurization slag, and the pulverization degree of the modified KR desulfurization slag was significantly improved.
[0052] refer to Figure 4 , Figure 5 As shown, it can be observed that the unmodified KR refined slag undergoes obvious pulverization after cooling. The modified KR desulfurization slag obtained in this embodiment after cooling is in granular or lumpy form, and the degree of pulverization is significantly improved.
[0053] The solidification rate of the modified KR desulfurization slag cooled to room temperature was measured, and 1517 kg of modified KR desulfurization slag was obtained. 11.09 kg of industrial salt was used, the mass of ilmenite added was 27.65 kg, and 1593 kg of KR desulfurization slag was used. The total raw materials used were 1631.74 kg. The solidification rate was calculated based on the ratio of the mass of the modified KR desulfurization slag to the raw materials used. The solidification rate in this embodiment is 93%.
[0054] Example 2
[0055] The present embodiment provides a method for solidifying KR desulfurized slag, which is carried out at the No. 1 operating table in the molten iron pretreatment workshop of the steelmaking plant of Changjiang Iron and Steel Group Co., Ltd. in Maanshan City, Anhui Province. The KR desulfurized slag of the furnace numbered 1# is taken, the temperature of which is 1321°C, the slag amount is 1644kg, and the composition of the desulfurized slag is shown in Table 2. The curing agent used is Na salt and a raw material containing TiO2, wherein the Na salt used is industrial salt and the raw material containing TiO2 is ilmenite. The above raw materials are all provided by Changjiang Iron and Steel Group Co., Ltd. in Maanshan City, Anhui Province. The effective component of the industrial salt used is NaCl, and the effective component of the ilmenite is TiO2. The effective component percentage of the industrial salt is 95%, and the effective component percentage of the ilmenite is 53%.
[0056] Table 2 KR desulfurization slag composition of Example 2 (wt%)
[0057] Component TFe CaO <![CDATA[SiO2]]> Al2O3 MgO S other Proportion 26 48.81 12.33 1.17 1.10 1.08 9.51
[0058] A solidification method of KR desulfurization slag in this embodiment includes the following steps:
[0059] S1, adding the curing agent composed of the above industrial salt and ilmenite to the surface of KR desulfurization slag;
[0060] The dosage formula of the curing agent is the same as that in Example 1, k1 is selected as 0.31% in this embodiment; k2 is selected as 0.8% in this embodiment, and the mass of industrial salt added is 13.64 kg, and the mass of ilmenite added is 24.82 kg.
[0061] S2, stirring and mixing, according to the incoming mass of molten iron and the size of the ladle, calculating the stirring height, the corresponding stirring speed and the stirring time;
[0062] In this embodiment, the mass of the incoming molten iron is 328.91t, and the density of the molten iron is 7138kg / m 3 , volume is 46.07m 3 .
[0063] The definition of stirring height in this embodiment is the same as that in Example 1, the calculation formula of stirring height is the same as that in Example 1, and h1 is 3.71m, h2 is 3.52m, and h3 is 3.32m. The calculation formula of stirring speed is the same as that in Example 1, and v1 is 75r / min, v2 is 85r / min, and v3 is 95 / min. The calculation formula of stirring time is the same as that in Example 1, and the corresponding stirring time is 30s.
[0064] S3, slag pouring: pour the reformed KR desulfurization slag into the slag pot, and plan the slag pot according to the slag volume.
[0065] S4. Send the slag pot to the slag treatment plant for baking. The baking temperature is 1200 degrees and the baking time is 45 minutes.
[0066] S5. Let the slag pot stand and cool to room temperature, then turn the slag pot over, pour the KR desulfurization slag after standing into the slag pit, keep the slag pit dry without water accumulation, and obtain modified KR desulfurization slag.
[0067] The composition of the modified desulfurization slag was measured. After modification, the composition of the obtained desulfurization slag was roughly the same as that of the unmodified KR desulfurization slag, and the pulverization degree of the modified KR desulfurization slag was significantly improved.
[0068] The solidification rate of the modified KR desulfurization slag cooled to room temperature was measured, and the solidification rate of this embodiment was 98%.
[0069] Example 3
[0070] The present embodiment provides a method for solidifying KR desulfurized slag, which is carried out at the No. 1 operating table in the molten iron pretreatment workshop of the steelmaking plant of Changjiang Iron and Steel Group Co., Ltd. in Maanshan City, Anhui Province. The KR desulfurized slag of the furnace No. 2 is taken, the temperature of which is 1305°C, the slag amount is 1572kg, and the composition of the desulfurized slag is shown in Table 3. The curing agent used is Na salt and a raw material containing TiO2, wherein the Na salt used is industrial salt, and the raw material containing TiO2 is ilmenite. The above raw materials are all provided by Changjiang Iron and Steel Group Co., Ltd. in Maanshan City, Anhui Province. The effective component of the industrial salt used is NaCl, and the effective component of the ilmenite is TiO2. The effective component percentage of the industrial salt is 95%, and the effective component percentage of the ilmenite is 53%.
[0071] Table 3 KR desulfurization slag composition of Example 3 (wt%)
[0072] Component TFe CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO S other Proportion 22 52.38 14.03 1.85 1.26 1.24 7.24
[0073] A solidification method of KR desulfurization slag in this embodiment includes the following steps:
[0074] S1, adding the curing agent composed of the above industrial salt and ilmenite to the surface of KR desulfurization slag;
[0075] The dosage formula of the curing agent is the same as that in Example 1, k1 is selected as 0.23% in this embodiment; k2 is selected as 1% in this embodiment, and the mass of industrial salt added is 9.68 kg, and the mass of ilmenite added is 29.66 kg.
[0076] S2, stirring and mixing, according to the incoming mass of molten iron and the size of the ladle, calculating the stirring height, the corresponding stirring speed and the stirring time;
[0077] In this embodiment, the mass of molten iron is 314.51 tons, and the density of molten iron is 7138 kg / m 3 , volume is 44.06m 3 The definition of stirring height in this embodiment is the same as that in embodiment 1, and the calculation formula of stirring height is the same as that in embodiment 1, and it is obtained that h2 is 3.57m, h3 is 3.38m, and h4 is 3.20m. The calculation formula of stirring speed is the same as that in embodiment 1, and it is obtained that v1 is 73r / min, v2 is 83r / min, and v3 is 93 / min. The calculation formula of stirring time is the same as that in embodiment 1, and the corresponding stirring time is 30s.
[0078] S3, slag pouring: pour the reformed KR desulfurization slag into the slag pot, and plan the slag pot according to the slag volume.
[0079] S4. Send the slag pot to the slag treatment plant for baking. The baking temperature is 1000 degrees and the baking time is 75 minutes.
[0080] S5. Let the slag pot stand and cool to room temperature, then turn the slag pot over, pour the KR desulfurization slag after standing into the slag pit, keep the slag pit dry without water accumulation, and obtain modified KR desulfurization slag.
[0081] The composition of the modified desulfurization slag was measured. After modification, the composition of the obtained desulfurization slag was roughly the same as that of the unmodified KR desulfurization slag, and the pulverization degree of the modified KR desulfurization slag was significantly improved.
[0082] The solidification rate of the modified KR desulfurized slag cooled to room temperature was measured, and the solidification rate of this embodiment was 90%.
[0083] Comparative Example 1
[0084] The difference between this comparative example and Example 1 is that the curing agent used is Na salt, wherein the Na salt used is industrial salt, wherein the percentage of effective ingredients of the industrial salt is 95%, and k1 in the embodiment is the addition coefficient of Na ions, and its value range is between 0.23% and 0.31%, and 0.26% is selected in this comparative example; other operations are basically the same.
[0085] The composition of the modified desulfurized slag was measured. After modification, the composition of the obtained desulfurized slag was roughly the same as that of the unmodified KR desulfurized slag.
[0086] The solidification rate of the modified KR desulfurization slag cooled to room temperature was measured, and the solidification rate of the comparative example was 68%.
[0087] Comparative Example 2
[0088] The difference between this comparative example and Example 1 is that the curing agent used is Na salt, wherein the Na salt used is industrial salt, wherein the percentage of effective ingredients of the industrial salt is 95%, and k1 in the embodiment is the addition coefficient of Na ions, and its value range is between 0.23% and 0.31%, and 0.52% is selected in this comparative example; other operations are basically the same.
[0089] The composition of the modified desulfurized slag was measured. After modification, the composition of the obtained desulfurized slag was roughly the same as that of the unmodified KR desulfurized slag.
[0090] The solidification rate of the modified KR desulfurized slag cooled to room temperature was measured, and the solidification rate of the comparative example was 75%.
[0091] Comparative Example 3
[0092] The difference between this comparative example and Example 1 is that the curing agent used is TiO2, the raw material containing TiO2 used is ilmenite, wherein the effective component percentage of ilmenite is 53%, and k2 in the embodiment is the addition coefficient of ilmenite, and its value range is between 0.8 and 1%, and 0.92% is selected in this comparative example. The other operations are basically the same.
[0093] The composition of the modified desulfurized slag was measured. After modification, the composition of the obtained desulfurized slag was roughly the same as that of the unmodified KR desulfurized slag.
[0094] The solidification rate of the modified KR desulfurization slag cooled to room temperature was measured, and the solidification rate of the comparative example was 60%.
[0095] Comparative Example 4
[0096] The difference between this comparative example and Example 1 is that the curing agent used is TiO2, the raw material containing TiO2 used is ilmenite, wherein the effective component percentage of ilmenite is 53%, k2 in the embodiment is the addition coefficient of ilmenite, and its value range is between 0.8 and 1%, and 2% is selected in this comparative example. The other operations are basically the same.
[0097] The composition of the modified desulfurized slag was measured. After modification, the composition of the obtained desulfurized slag was roughly the same as that of the unmodified KR desulfurized slag.
[0098] The solidification rate of the modified KR desulfurization slag cooled to room temperature was measured, and the solidification rate of the comparative example was 67%.
[0099] Comparative Example 5
[0100] The difference between the operation of this comparative example and that of Example 1 is that the curing agent is magnesite, and the amount added is 4-6% of the mass of silicon dioxide in the KR desulfurization slag, calculated based on the effective component B2O3 of magnesite. The other operating steps are the same.
[0101] The composition of the modified desulfurized slag was measured. After modification, the composition of the obtained desulfurized slag was roughly the same as that of the unmodified KR desulfurized slag.
[0102] The solidification rate of the modified KR desulfurization slag cooled to room temperature was measured, and the solidification rate of this embodiment was 70%.
[0103] The modified desulfurized slag prepared in Example 1 to Example 3 can be recycled into the converter as a slag-forming agent for refining high-sulfur free-cutting steel.
Claims
1. A method for solidifying KR desulfurization slag, characterized in that: include: Before slagging, a curing agent is added into the ladle to make the KR desulfurized slag fully contact / mix with the curing agent; wherein the curing agent comprises Na salt and TiO2; The KR desulfurization slag mixed with the solidifying agent is cooled to below the phase transition temperature of β-phase dicalcium silicate to γ-phase dicalcium silicate, thereby achieving the solidification treatment of the KR desulfurization slag.
2. The solidification method of KR desulfurization slag according to claim 1, characterized in that: The raw material of the Na salt is pure NaCl or industrial salt; and / or the addition amount of the Na salt is 0.23% to 0.31% of the mass of the KR desulfurization slag in terms of Na ions.
3. The solidification method of KR desulfurization slag according to claim 1, characterized in that: The added amount of TiO2 is 0.8-1% of the mass of the KR desulfurization slag.
4. The method for solidifying KR desulfurization slag according to claim 3, characterized in that: The raw material of TiO2 is ilmenite.
5. The solidification method of KR desulfurization slag according to any one of claims 1 to 4, characterized in that: After adding the curing agent into the ladle, the KR desulfurization slag and the curing agent are fully contacted / mixed by stirring.
6. The method for solidifying KR desulfurization slag according to claim 5, characterized in that: The stirring is performed to fully contact / mix the KR desulfurization slag with the curing agent, specifically, the curing agent is added to the surface of the KR desulfurization slag, and the molten iron under the KR desulfurization slag is stirred to make the KR desulfurization slag and the curing agent evenly mixed; The stirring heights are h1=0.95h, h2=0.9h, h3=0.85h, where h represents the height of the molten iron in the ladle; The corresponding stirring speeds are The unit of stirring speed is r / min.
7. The solidification method of KR desulfurization slag according to any one of claims 1 to 4, characterized in that: Also includes: Before cooling, the KR desulfurization slag mixed with the solidifying agent is poured into a slag pot; and / or the KR desulfurization slag mixed with the solidifying agent is baked.
8. The method for solidifying KR desulfurization slag according to claim 7, characterized in that: The KR desulfurization slag mixed with the curing agent is baked, specifically, the baking temperature is selected to be 1000-1200° C., and the baking time is 45-75 minutes.
9. The solidification method of KR desulfurization slag according to any one of claims 1 to 4, characterized in that: The cooling is specifically natural cooling, and / or cooling the KR desulfurization slag mixed with the solidifying agent to room temperature.
10. A modified KR desulfurization slag, characterized in that: The desulfurized slag is prepared by the solidification method of KR desulfurized slag according to any one of claims 1 to 9, and the solidification rate reaches more than 90%.
Citation Information
Patent Citations
Slag solidifying agent for AOD (argon oxygen decarburization) refining stainless steel smelting slag and preparation method and application thereof
CN113957202A
Method for curing KR desulfurization slag and product obtained by method
CN117965825A